Re-planning of flight routes avoiding convective weather and the "three areas" - Lim, Wen-Xian (2020)
The air traffic volume is expected to experience substantial growth globally in the foreseeable future. This increase poses a serious test to the capability of the air traffic management (ATM) system in sustaining the efficiency and safety levels of the air traffic flow. As such, enhancing the performance capability of the ATM system had become a key focus of research within the aviation industry in recent years. Bad weather has always been a key contributor to flight accidents. Therefore, the avoidance of the regions in which adverse weather conditions exist is of paramount importance to the safe completion of flights. Convective weather is a common example of such weather conditions. In a similar manner, there also exist areas in the airspace that should be avoided during a flight for safety considerations. They are namely the prohibited area, restricted area, and danger area, collectively referred to as the 'three areas'. In this paper, a route re-planning mechanism based on the cellular automaton model was studied. The objective is to create flight routes that avoid both the 'three areas' and regions of convective weather en-route with as minimum an impact on the flight distance as possible. Simulations were carried out using the model to create such flight routes for a selected section of the airspace of Myanmar. Simulations were completed under different scenarios. The simulation results showed successful avoidance of all the 'three areas' and the hypothetical regions of convective weather conditions.